Simultaneously monitoring DNA binding and helicase-catalyzed DNA unwinding by fluorescence polarization - Xu, H. Q. (Oxford University Press, 2003)
A new method for helicase-catalyzed DNA unwinding is described. This assay takes advantage of the substantial change in fluorescence polarization (FP) upon helicase binding and DNA unwinding. The low anisotropy value, due to the fast tumbling of the free oligonucleotide in solution, increases abruptly upon binding of helicase to the fluorescein-labeled oligonucleotide. The high anisotropy of the helicase– DNA complex decreases as the fluorescein-labeled oligonucleotide is released from the complex through helicase-catalyzed DNA unwinding. This FP signal can be measured in real time by fluorescent spectroscopy. This assay can simultaneously monitor DNA binding and helicase-catalyzed DNA unwinding. It can also be used to determine the polarity in DNA unwinding mediated by helicase. This FP assay should facilitate the study of the mechanism by which helicase unwinds duplex DNA, and also aid in screening for helicase inhibitors, which are of growing interest as potential anticancer agents.